The effects of virtual-augmented reality training on anxiety among operating room students attending coronary artery bypass graft surgery - Fereshteh Sargolzaei; Athar Omid; Mohsen Mirmohammad-Sadeghi; Ahmad Ghadami (Kashan University of Medical Sciences, 2021)
Background: Operating room (OR) students experience varying levels of anxiety during their internship program in the OR. Educational technology has the potential for reducing anxiety. Objectives: This study aimed at assessing the effects of training based on virtual-augmented reality (VAR) on anxiety among OR students attending coronary artery bypass graft (CABG) surgery. Methods: This randomized controlled trial was conducted in 2020. Thirty-six OR students were conveniently recruited and randomly allocated to an intervention (n = 18) and a control (n = 18) group. Participants in the control group received conventional training, whereas their counterparts in the intervention group received VAR training through watching a 360-degree VAR video of CABG surgery in addition to conventional training. The State-Trait Anxiety Inventory was used for anxiety assessment in both groups at three time points, namely before entering the OR on the first day of the internship program, after entering the OR but before scrub, and on the last day of the program. The data were analyzed through the independent-samples t test, the Chi-square test, and the repeated-measures analysis of variance. Results: There was no significant difference between the intervention and the control groups regarding the pretest mean scores of state anxiety (40.61 ± 7.63 vs. 41.59 ± 5.09; P = 0.66) and trait anxiety (39.17 ± 7.39 vs. 39.29 ± 6.05; P = 0.96). However, the mean scores of state and trait anxiety in the intervention group were significantly less than the control group at both the first posttest (33.17 ± 6.16 vs. 45.06 ± 8.69 and 33.56 ± 6.19 vs. 42.59 ± 6.62; P < 0.001) and the second posttest (32.39 ± 4.62 vs. 42.35 ± 6.14 and 32.94 ± 5.20 vs. 41.0 ± 5.58; P < 0.001). Conclusion: VAR training is effective in significantly reducing anxiety among OR students attending CABG surgery.